Returns to Inventors - Otto Toivanen; Lotta Väänänen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
A key input to inventive activity is human capital. Hence it is important to understand the monetary incentives of inventors. We estimate the effect of patented inventions on individual earnings by linking data on U.S. patents and their inventors to Finnish employer-employee data. Returns are heterogeneous: Inventors get a temporary reward of 3% of annual earnings for a patent grant and for highly-cited patents a longer-lasting premium of 30% in earnings three years later. Similar medium-term premia accrue to inventors who initially hold the patent rights, although they forego earnings at the time of the grant.
urn:nbn:de:bvb:19-epub-13245-0
Keywords: 330; citations; effort; incentives; inventors; intellectual property; patents; performance pay; return; wages; Industrieforschung; Innovation; Patent; Immaterialgüterrechte; Leistungsentgelt; Finnland; USA